Gradualidade e dependência de perspectiva nos adjetivos do português brasileiro - Marques, Marina Nishimoto (2024)
Among the adjectives we find in the natural languages, there are those which predicate binary properties from the objects that are characterised by them (e.g. ‘federal’), and also those which relate said objects to (a degree in) a scale (e.g. ‘tall’) – the latter are the scalar adjectives. Among the scalar adjectives, we can find those who are related to objectively measurable scales in the world (such as ‘tall’), and those that must be relativised to the perspective of a speaker in order to be semantically interpreted (such as ‘beautiful’). This relativisation is necessary because these items talk about properties that vary in their distribution depending on the speaker (or on the individual that judges the sentence). Scalar adjectives that are dependent on perspective are this work’s focus, and will be called ‘subjective (scalar) adjectives’. In this thesis, we investigate some properties that differentiate those items from non-subjective scalar adjectives (especially perspective dependence and scalar variation which is not objectively measurable). Based on data from Brazilian Portuguese (BP), we determine what types of adjectives fit in the group of the subjective adjectives. Furthermore, we show how the peculiarities of the subjective adjectives make their behaviour different from other items when they find themselves in environments of comparison and scalar modification.